THE ECONOMICS OF THE VALUE OF HUMAN LIFE: CONTRIBUTION TO THE EUTHANASIA DEBATE - Begović, Boris (Pravni zapisi, 2026)
The paper examines the economics of the value of human life, seeking a suitable input that would make a relevant contribution to the euthanasia debate, focusing on the legal status of euthanasia, specified in the paper as “voluntary as- sisted dying”, especially in the key disputes in that debate. The paper looks at three economic models of the value of human life: the model of the value of statistical life, the model of the objective value of human life, and the model of the subjective value of human life. These models were evaluated for their suitability in providing inputs to the euthanasia debate, and only the subjective value model passed the evaluation. The most significant input from the economic model is the proposition that only “voluntary euthanasia” should be legalized as a last resort measure and that the decision-making process should be strictly regulated and specified in detail in legislation. Regulation guidelines are provided, as are guidelines for further research.